Faktor-Faktor Yang Menyebabkan Kejadian Shivering Pada Pasien Sectio Caesarea Dengan Spinal Anestesi Di Rsud Banyumas - Rusnowanto, Rusnowanto; Sodikin, Sodikin; Solikhah, Umi; Elsanti, Devita (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Background: Shivering events during June - August 2022 obtained an average number of cesarean section actions of 106 - 110 actions per month. Of these, 53 people or 49.05% of sectio caesaria patients experienced shivering. There are several factors that can influence the incidence of shivering including age, length of operation, exposure to cold temperatures, LILA, and needle size. Objective: To determine the factors that cause shivering in sectio caesaria patients with spinal anesthesia at Banyumas Hospital. Methods: This research is a type of analytic observational study with a cross sectional approach with a random sampling technique and obtained a sample of 40 sectio caesarea patients. The analysis used is Logistic Regression. Results: There is a significant relationship between length of operation (p 0.019), operating room temperature (p 0.004), LILA (p 0.030). Conclusion: The most dominant factor affecting the incidence of shivering is body temperature (p 0.008; OR 13.1).